2008
DOI: 10.2478/s11756-008-0124-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of metabolic enzyme genes and heat-shock protein genes during embryonic development in diapause and non-diapause egg of multivoltine silkworm Bombyx mori

Abstract: The expression of metabolic enzyme genes and heat-shock protein genes (Hsp) during early embryogenesis in diapause and non-diapause eggs of the silkworm Bombyx mori was quantified by semi-quantitative RT-PCR. The trehalase gene (Tre) was expressed in non-diapause eggs up-to nine days, while in diapause eggs was not up regulated. The glycogen phosphorylase gene (GPase) was expressed in non-diapause eggs, whereas in diapause eggs a high level was observed in early stage, but down regulated in later stage. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Many sHsps exist as oligomers and can have molecular masses up to 800 kDa (MacRae, 2000) with the α‐crystallin domain and N‐ and C‐terminal tails all having roles in the oligomer formation (Haslbeck et al , 2005). In addition to stress response, sHsps are produced during normal developmental stages in insects (Mason et al , 1984; Michaud et al , 1997; Joanisse et al , 1998; Shirk et al , 1998; Sonoda et al , 2006; Saravanakumar et al , 2008; Kokolakis et al , 2009), but their functional roles remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Many sHsps exist as oligomers and can have molecular masses up to 800 kDa (MacRae, 2000) with the α‐crystallin domain and N‐ and C‐terminal tails all having roles in the oligomer formation (Haslbeck et al , 2005). In addition to stress response, sHsps are produced during normal developmental stages in insects (Mason et al , 1984; Michaud et al , 1997; Joanisse et al , 1998; Shirk et al , 1998; Sonoda et al , 2006; Saravanakumar et al , 2008; Kokolakis et al , 2009), but their functional roles remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are strong correlations between Aphelenchus auenae survival in dry air and glycerol and trehalose contents were observed . A large number of trehalose that accumulates in the hemolymph is derived from fat body glycogen in the diapausing pupae of Philosamia cynthia pryeri (Hayakawaa and Chino, 1981), which was studied by Saravanakumar et al (2008). The trehalase gene was expressed in non-diapause eggs of the multivoltine silkworm Bombyx mori for 9 days, whereas that in the diapause eggs was not upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…The bivoltine silkworm eggs enter diapause and hatch after four months preservation under 5º C. Alternatively, the diapause can be broken by treating the eggs with HCl immediately after oviposition. Reports have indicated that Tre, GPase, G6PD and SDH genes expressed at different levels in various target tissues of B. mori are actively involved in the diapause process and in the eggs, diapausing is completed by 24-36 h (Sakano et al 2004;Saravanakumar et al 2008;Ponnuvel et al 2010). The present study is an analysis of the expression of selected metabolic enzymes, translational regulatory gene and HSP genes within 48 h of oviposition in both the diapause and HCl treated (non-diapause) bivoltine silkworm eggs.…”
Section: Discussionmentioning
confidence: 99%
“…As the onset of diapause occurs predominantly in the early stage, i.e., within 30h of oviposition, it is worth analyzing the differential gene expression at this crucial period to find out the significant up-as well as downregulation of diapause related genes involved in non-diapause process. Earlier findings indicated that few metabolic and heat shock protein genes were differentially expressed during the onset of diapause (Saravanakumar et al 2008;Ponnuvel et al 2010). Based on the available information, an attempt has been made to investigate the molecular aspects of these major genes involved in diapause phenomenon in HCl treated (non-diapause) and untreated (diapause) eggs during early embryogenesis.…”
Section: Introductionmentioning
confidence: 99%